Comparing effectiveness of first‐line antiretroviral therapy between peri‐urban and rural clinics in KwaZulu‐Natal, South Africa. Issue 7 (12th January 2022) - Brijkumar, Jaysingh; Edwards, Johnathan A.; Johnson, Brent A.; Ordonez, Claudia; Sunpath, Henry; Lee, Mitch; Dudgeon, Mathew R.; Rautman, Lydia; Pillay, Selvan; Moodley, Pravi; Sun, Y. V.; Castillo‐Mancilla, José; et al.
Abstract: Objectives: Viral suppression (VS) is the hallmark of successful antiretroviral therapy (ART) programmes. We sought to compare clinic retention, virological outcomes, drug resistance and mortality between peri‐urban and rural settings in South Africa after first‐line ART. Methods: Beginning in July 2014, 1000 (500 peri‐urban and 500 rural) ART‐naïve patients with HIV were enrolled and managed according to local standard of care. Clinic retention, virological suppression, virological failure (VF), genotypic drug resistance and mortality were assessed. The definition of VS was a viral load ≤1000 copies/ml. Time to event analyses were stratified by site, median age and gender. Kaplan–Meier curves were calculated and graphed with log‐rank modelling to compare curves. Results: Based on 2741 patient‐years of follow‐up, retention and mortality did not differ between sites. Among all 1000 participants, 47%, 84% and 91% had achieved VS by 6, 12 and 24 months, respectively, which was observed earlier in the peri‐urban site. At both sites, men aged < 32 years had the highest proportion of VF (15.5%), while women aged > 32 years had the lowest, at 7.1% ( p = 0.018). Among 55 genotypes, 42 (76.4%) had at one or more resistance mutations, which did not differ by site. K103N (59%) and M184V (52%) were the most common mutations, followed by V106M and K65R (31% each). Overall, death was infrequent (< 4%). Conclusions: No significant differences in treatment outcomes between peri‐urban and rural clinics were observed. In both settings, young men were especially susceptible to clinic attrition and VF. More effective adherence support for this important demographic group is needed to achieve UNAIDS targets.